Steroid sulfatase is a potential modifier of cognition in attention deficit hyperactivity disorder - Stergiakouli, E.; Langley, K.; Williams, H.; Walters, J.; Williams, N. M.; Suren, S.; Giegling, I.; Wilkinson, L. S.; Owen, M. J.; O'Donovan, M. C.; Rujescu, D.; Thapar, A.; et al. (Genes, brain and behavior, 2011)
Deletions encompassing the X‐linked STS gene (encoding steroid sulfatase) have been observed in subjects with neurodevelopmental disorders, including attention deficit hyperactivity disorder (ADHD). Recently, two single nucleotide polymorphisms (SNPs) within STS (rs12861247 and rs17268988) have been reported to be associated with ADHD risk and inattentive symptoms in ADHD, respectively. Using a UK sample of ADHD subjects (aged 5–18 years), we tested the hypothesis that rs12861247 is associated with ADHD risk using a case–control approach (comparing 327 ADHD cases with 358 male controls from the Wellcome Trust Case Control Consortium). Using a subset of males from the ADHD sample, we also examined whether variation within STS is associated with symptomatology/cognitive function in ADHD. We then tested whether SNPs associated with cognitive function in ADHD were also associated with cognitive function in healthy male subjects using a German sample (n = 143, aged 18–30 years), and whether STS was expressed in brain regions pertinent to ADHD pathology during development. We did not replicate the previously identified association with rs12861247. However, in ADHD males, variation at rs17268988 was associated with inattentive symptoms, while variation within STS was significantly associated with performance on three cognitive measures. Three SNPs associated with cognitive function in ADHD males were not associated with cognitive function in healthy males. STS was highly expressed in the developing cerebellar neuroepithelium, basal ganglia, thalamus, pituitary gland, hypothalamus and choroid plexus. These data suggest that genetic variants affecting STS expression and/or activity could influence the function of brain regions perturbed in ADHD.